Body Fat Mass is Better Indicator than Indirect Measurement Methods in Obese Children for Fatty Liver and Metabolic Syndrome - Masallah Baran; Kivanc Celikkalkan; Yeliz Cagan Appak; Miray Karakoyun; Mehmet Bozkurt; Cemil Kocyigit; Ali Kanik; Bumin Nuri Dundar (Ital Publication, 2019)
Introduction: To compare the bioelectric impedance analysis (BIA) with indirect measurement methods in the evaluation of obese children. To determine the diagnostic value of BIA in the fatty liver and metabolic syndrome (MS) in obese children.  Population and methods: One hundred thirty-four obese children whom ≥10 years of age were prospectively assessment. All patients were evaluated by foot to foot BIA and indirect measurement methods. Blood biochemical parameters such as glucose, lipids and insulin levels were studied and oral glucose tolerance test was performed. Fatty liver was assessed by ultrasonography. Compared BIA records and indirect measurements findings according to fatty liver and MS. Results: The study included females/males: 77/57, mean age of 13.3 ± 2.2 years. Fatty liver was detected in 94 patients, MS was diagnosed in 58 cases. There were no gender difference in terms of fatty liver and MS. Fatty liver was seen more frequently in patients with metabolic syndrome than in those without metabolic syndrome (p < 0.001). Fat Mass (FM) of ≥ 97th percentile was observed in 63% of the 94 patients with fatty liver versus 37.5% of 40 patients without fatty liver. A FM of ≥97th percentile was observed in 72% (n=42) of the 58 patients with metabolic syndrome, 42% (n=33) of 76 patients without MS. Body mass index, upper mid-arm circumference, waist circumference (WC), and hip circumference values were significantly increased in patients with fatty liver. There was a better correlation was determined between FM and FM Index with fatty liver compared to indirect measurement methods. BIA records were found moderately correlated with indirect measurements. Conclusion: Our results revealed that FM and FMI have a better correlated in obese children with fatty liver and metabolic syndrome than indirect measurement methods. The measurement of body FM by BIA can be used together with the indirect measurement methods to detect the fatty liver. FMI may be an alternative diagnostic criterion instead of WC for diagnosis of MS in children.